A wizard of earthsea ebook - Le Guin, Ursula K. (Earthsea, 2012)
The first novel of Ursula K. Le Guin's must-read Books of Earthsea. Ged was the greatest sorcerer in Earthsea, but in his youth he was the reckless Sparrowhawk. In his hunger for power and knowledge, he tampered with long-held secrets and loosed a terrible shadow upon the world. This is the tumultuous tale of his testing, how he mastered the mighty words of power, tamed an ancient dragon, and crossed death's threshold to restore the balance. With stories as perennial and universally beloved as The Chronicles of Narnia and The Lord of the Rings—but also unlike anything but themselves—Ursula K. Le Guin's Earthsea novels are some of the most acclaimed and awarded works in literature. They have received accolades such as the National Book Award, a Newbery Honor, the Nebula Award, and many more honors, commemorating their enduring place in the hearts and minds of readers and the literary world alike. Join the millions of fantasy readers who have explored these lands. As The Guardian put it: "Ursula Le Guin's world of Earthsea is a tangled skein of tiny islands cast on a vast sea. The islands' names pull at my heart like no others: Roke, Perilane, Osskil . . ." The Books of Earthsea include: A Wizard of Earthsea The Tombs of Atuan The Farthest Shore Tehanu Tales from Earthsea The Other Wind